The opportunity index : a solution-based framework to dismantle the racial wealth gap - Lewis, Gavin (Managing director of BlackRock) (John Wiley & Sons, Inc., 2023)
"A bold and fresh perspective unravelling the economics of racial inequality In The Opportunity Index, BlackRock Managing Director and co-founder of the #Talkaboutblack movement, Gavin Lewis, skillfully plots the origins of the racial wealth gap and its impact on the inequalities faced by the Black community today. Weaving a personal and at times moving narrative through some of the most disruptive events of our time, he offers a blueprint for businesses and individuals to understand the risks and opportunities presented by inequality and issues an urgent call to action"--